Percutaneous transluminal angioplasty in a patient with chronic cerebrospinal venous insufficiency and persistent left superior vena cava. (April 2014) - Lupattelli, T; Benassi, F; Righi, E; Bavera, P; Bellagamba, G
Chronic cerebrospinal venous insufficiency (CCSVI) is a syndrome characterized by stenoses of the internal jugular veins (IJVs) and/or azygos veins and formation of collateral venous channels. A case of a 57-year-old patient with CCSVI in whom the venous outflow from the left IJV to the right atrium occurred through a venous anomaly, the persistent left superior vena cava (PLSVC), is reported. PLSVC is caused by persistence of the left anterior cardinal vein that drains blood from the limb effluent from the left and the left side of head and neck into coronary sinus (Type a), or in the left atrium (Type b). PLSVC can be associated either with innominate vein hypoplasia or other congenital heart abnormalities. Because of evidence of left innominate vein hypoplasia, angioplasty was not performed using the ordinary route but passing with the balloon directly through the PLSVC up to the left IJV. Finally, angioplasty was carried out in a standard manner in the right IJV as well as in the azygous vein. Confirmation angiogram revealed complete reopening of all treated vessels with no evidence of peri- and postoperative complications. The patient was discharged home the following day in good general conditions. PLSVC is a rare congenital vein anomaly but in case of concomitant innominate vein hypoplasia may prove to be a valuable alternative to treat patients with IJV diseases.